Regulación de redes sociales como medios de comunicación digitales dentro de la ley electoral, código de la democracia para el control de la campaña electoral anticipada - Ludeña Briceño, Miguel Ángel (2023)
The advance of technology and science in our country has allowed us to take a giant step towards the technification of communication; the growing new ways of communicating and informing ourselves are leaving traditional media to one side. Nowadays, social networks are within the reach of almost everyone; I could say with certainty that 80% of Ecuadorians have at some time logged on to a social network and many of them even have personal profiles on them. It is almost impossible to find a person who does not have a smartphone with which he or she spends several hours connected to the network, as many of us have turned the mobile phone into a tool for work and recreation. Politicians find the virtual world very attractive, as they understood that through the Internet, they could disseminate their ideas faster and have a more personal interaction with citizens. However, just as new information technologies are advancing, so must the law. Within our electoral panorama, the networks play the main role of being the great disseminators of information, since with a single click we can access any information. What is important and transcendental for users is knowing how to distinguish false information from true information. Likewise, interviews and surveys were carried out with legal professionals, political subjects and social communicators. The results obtained were used to propose a legal proposal to the Democracy Code with the aim of implementing the regulation of social networks as digital media for the control of early electoral campaigning.